A Comparative Analysis of Hydrogen Storage Characteristics in AZ31 Magnesium Alloy with the Addition of Graphene and Carbon Nanotubes via Ball Milling Process - Huang, Song-Jeng; Lin, Wei-Da; Rajagopal, Veeramanikandan (Journal of Research Updates in Polymer Science, 2023)
In the present investigation, an examination was conducted on the hydrogen storage performance of industrial waste grade AZ31 magnesium alloy when combined with either Carbon Nanotubes or Graphene. This study aims to understand the enhancement of hydrogen storage properties reinforced with polymer materials, such as Graphene or Carbon Nanotubes. The experimental samples, composed of AZ31 Magnesium Alloy combined with either Carbon Nanotubes or Graphene, were crafted through gravity casting. Thereafter, a high-energy ball milling process was employed to further refine the hydrogen storage material powders. The micrographic structures of all the sample powders were analyzed by x-ray diffraction (XRD), and scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS). Additionally, the average particle size distributions of the sample powders were quantified for comprehensive characterization. The absorbed and desorbed hydrogen capacity and kinetics was calculated by a Sievert’s type apparatus. Overall, the performance of the sample powder AZ31-0.1G showed the highest absorption and desorption at a rate of 0.0036 wt%/s and 0.0084 wt%/s. Moreover, the hydrogen capacity of AZ31-0.1G reached the highest value at 5.32 wt%. The acquired data unveils that with the adding of either Graphene or Carbon Nanotubes as additives significantly improved the hydrogen storage capacity of AZ31 magnesium alloy.